Výkonnost podniku v kontextu spokojenosti zákazníka, zpětných toků, kvality, inovací a znalostí - Klapalová, Alena (Masaryk University Press, 2020)
Title in English: Business performance in the context of customer satisfaction, backflows, quality, innovation and knowledge. The subject of this publication is the research of customer satisfaction and its connection with company performance, quality, innovation and knowledge. The main goal is to analyse the mutual relations of the above factors, including their systematisation on the basis of empirical findings in companies across industries in the Czech Republic. The publication offers a theoretical analysis of the basic relationships of the above factors and discusses them with the results of the analysis of primary data from companies. The purpose is to clarify to what extent connections assumed in the literature are reflected in the Czech environment and how much they influence the subjective and objective performance of companies. Both types of indicators were used in the construction of analytical models revealing that results based on them differ, and that models within the different indicators also differ.